Seropositivity of Brucella spp. and Leptospira spp. antibodies among abattoir workers and meat vendors in the city of Mwanza, Tanzania: A call for one health approach control strategies. - Mariam M Mirambo; Georgies F Mgode; Zakaria O Malima; Matata John; Elifuraha B Mngumi; Ginethon G Mhamphi; Stephen E Mshana (Public Library of Science (PLoS), 2018)
Brucellosis and leptospirosis are among neglected tropical zoonotic diseases particularly in the resource limited countries. Despite being endemic in these countries, there is paucity of information on its magnitude. This study investigated seropositivity of Brucella spp. and Leptospira spp., and associated factors among abattoir workers and meat vendors in the city of Mwanza, Tanzania.A community based cross-sectional study was conducted in Mwanza city from May to July 2017. Socio-demographic and other relevant information were collected. Detection of Brucella spp. and Leptospira spp. antibodies were done using slide agglutination test and microscopic agglutination test, respectively. Data were analyzed using STATA version 13 Software.A total of 250 participants (146 abattoir workers and 104 meat vendors) were enrolled with median age of 31 (IQR: 25-38) years. The overall, seropositivity of Brucella spp. antibodies was 48.4% (95% Cl: 42-54). Seropositivity of B. abortus was significantly higher than that of B. melitensis (46.0%, 95%Cl: 39-52 vs. 23.6%, 95% Cl: 18-28, P<0.001) while seropositivity of both species was 21.2% (95%Cl: 16-26). The seropositivity of Leptospira spp. was 10.0% (95% CI: 6-13) with predominance of Leptospira kirschneri serovar Sokoine which was detected in 7.2% of the participants. Being abattoir worker (OR: 2.19, 95% CI 1.06-4.54, p = 0.035) and long work duration (OR: 1.06, 95%CI: 1.01-1.11, p = 0.014) predicted presence of both B.abortus and B. melitensis antibodies. Only being married (p = 0.041) was significantly associated with seropositivity of Leptospira spp. Primary education was the only factor independently predicted presence of Brucella spp. antibodies among abattoir workers on sub-analysis of occupational exposure. None of factors were found to be associated with presence of Brucella spp. antibodies among meat vendors on sub-analysis.Seropositivity of B.abortus antibodies among abattoir workers and meat vendors is high and seem to be a function of being abattoir worker, having worked for long duration in the abattoir and having primary education. In addition, a significant proportion of abattoir workers and meat vendors in the city was seropositive for Leptospira kirschneri serovar Sokoine. There is a need to consider 'one health approach' in devising appropriate strategies to control these diseases in the developing countries.